Musicalization of a Line-Following Robot for Educational Robotics Competitions - Andrade, Jose Lindenberg De; Brandt, Guilherme Felix De Medeiros; Curvelo, Carla Da Costa Fernandes; Santana Junior, Orivaldo Vieira De; Alsina, Pablo Javier; Goncalves, Luiz M. G. (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
Educational Robotics competitions take place all over the world, with Robocup being the ultimate destination for most of these competitions. This is not different in Brazil. There are competitions for various educational levels, such as the Brazilian Robotics Competition (CBR) aimed at university students and the Brazilian Robotics Olympiad (OBR), intended for elementary and high school students. One of the categories in these competitions is the rescue category, where autonomous robots can be used to overcome challenges along a course, as well as rescue victims symbolized by objects. Various types of robots can be used in this category, utilizing wheels, chassis, claws, and sensors to assist in path detection, such as color, line, and proximity sensors. This category also has an extra challenge, where teams can present innovations in their own projects. In this sense, the project that performs best along the course and has the best innovation in the extra challenge earns points and can win the competition. One of the robots used in these competitions is from the project One Robot per Student (URA), of the Federal University of Rio Grande do Norte. The robot was designed both for use in competitions and for the training of teachers and teams. The use of music in Educational Robotics is a common approach and is known to be beneficial for education, but it is not as present in robotics competitions. Thus, as a matter of innovation, this work proposes to incorporate music into an autonomous robotics vehicle, in this case, the URA robot, making it a differentiating factor in educational robotics competitions. To achieve this, a buzzer actuator is attached to the URA vehicle's structure to produce sounds that signals the start and end of the vehicle's course in the rescue category challenge. These sounds are inserted into the programming through the frequencies of the melodies used in the URA vehicle's programming. The results of this work consider the effectiveness in competition environments within the rescue category in terms of functionality and performance.